2010
DOI: 10.1016/j.ajhg.2010.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the Gene Encoding the RER Protein FKBP65 Cause Autosomal-Recessive Osteogenesis Imperfecta

Abstract: On page 555 under the section titled Mutations in FKBP10 cause Recessive OI, there are two errors in the nomenclature for the identified mutations. The FKBP10 (NM_021939.3) mutation isolated in the Turkish cases (proband R06-113A) is c.321_353 del and is predicted to result in the deletion of eleven amino acids in the protein, p.Met107_Leu117 del. In the second paragraph of the subheading, the mutation in the Mexican-American family (proband R93-188) should be

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
123
1
3

Year Published

2010
2010
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(138 citation statements)
references
References 1 publication
11
123
1
3
Order By: Relevance
“…Accumulation of aggregated procollagen in the ER of FKBP65-deficient cells [12] indicates that FKBP65 is important for procollagen folding or trafficking. In vitro studies suggest that FKBP65 may stabilize the triple helix like HSP47 (Figure 3) and catalyze proline peptide bond isomerization [44], thus accelerating procollagen folding.…”
Section: Chaperoning Dilemma: Encouraging Success Vs Discouraging Famentioning
confidence: 99%
See 2 more Smart Citations
“…Accumulation of aggregated procollagen in the ER of FKBP65-deficient cells [12] indicates that FKBP65 is important for procollagen folding or trafficking. In vitro studies suggest that FKBP65 may stabilize the triple helix like HSP47 (Figure 3) and catalyze proline peptide bond isomerization [44], thus accelerating procollagen folding.…”
Section: Chaperoning Dilemma: Encouraging Success Vs Discouraging Famentioning
confidence: 99%
“…In vitro studies suggest that FKBP65 may stabilize the triple helix like HSP47 (Figure 3) and catalyze proline peptide bond isomerization [44], thus accelerating procollagen folding. However, no overhydroxylation or overglycosylation of lysines -- expected to accompany slower procollagen folding [45] -- has been detected in FKBP65-deficient cells [12]. Recent reports of OI with joint contractures (Bruck syndrome) in several patients with FKBP65 deficiencies [15, 16] might resolve this discrepancy.…”
Section: Chaperoning Dilemma: Encouraging Success Vs Discouraging Famentioning
confidence: 99%
See 1 more Smart Citation
“…In the other four individuals with OI type IV, exome sequencing revealed that one patient was compound heterozygous for a deletion of the entire exon 1 and a stopgain mutation in FKBP10 (data not shown), a gene associated with recessive OI 12. No conclusive result emerged from the analysis in the other three patients (table 1).…”
mentioning
confidence: 91%
“…Known defects include biallelic mutations in LEPRE1 [3-5], CRTAP [5,6], PPIB [7,8], BMP1 [9,10], and PLOD2 [11]. Mutations in chaperones (including Hsp47 ( SERPINH1 ) and FKBP10) impair intracellular collagen trafficking with intracellular retention or aggregation of collagen molecules and show dilation of the ER on electron microscopy, resulting in OI or related phenotypes [12-14]. Finally, rare other defects linked to distinct mechanisms involve the transcription factor osterix ( SP7 ) [15], pigment epithelium derived factor ( SERPINF1 ) [16] and transmembrane protein 38B ( TMEM38B ) [17,18].…”
Section: Introductionmentioning
confidence: 99%